THE INFLUENCE OF WORK ENVIRONMENT, COMPENSATION, AND JOB INSECURITY ON EMPLOYEE JOB SATISFACTION - Rizqia Amalia; Fajar Diaz Kusuma; Agung Priyono; Awang Darmawan Putra (Journal of Management and Leadership, 2026)
Employee job satisfaction is one of the important factors in supporting the achievement of company goals. There is a phenomenon of significant hotel revenue fluctuation during the 2023-2025 period, where drastic revenue increases were not accompanied by adequate system improvements. This study aims to analyze the influence of work environment, compensation, and job insecurity on employee job satisfaction at Golden Boutique Hotel Kemayoran. This research uses a quantitative approach with data collection through questionnaires and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4.1 application. The results show that work environment has no effect on employee job satisfaction (p-value 0.196); compensation has a positive and significant effect on employee job satisfaction (p-value 0.000), and job insecurity has no effect on employee job satisfaction (p-value 0.341). This research provides practical implications for hotel management to prioritize improvements in the compensation system as the main strategy to increase employee job satisfaction.